IMPROVING STUDENTS’ READING COMPREHENSION THROUGH PREVIEW, QUESTION, READ, SUMMARY, AND TEST METHOD OF VII GRADE AT MTs MADINATUL ILMI DDI SIAPO - Reza Aprilieah (Jurnal Madako Education, 2019)
This research is pre-experimental research design that aims to find whether or not the implementation of Preview, Question, Read, Summary, and Test method can improve the students’ reading comprehension of VII grade at MTs Madinatul Ilmi DDI Siapo. The subject of the research is the students of VII grade at MTs Madinatul Ilmi DDI Siapo which consists of 27 students. In this research used on Pre-test and Post-test. In the pre-test was used to measure the students’ previous improving students’ reading comprehension, the treatments were applying materials through Preview, Question, Read, Summary, and Test method , and the post-test was used to find out the students’ reading comprehension after given treatments. The results of the test show that the students’ mean score in pre-test is 76.19 while in the post-test improved up to 80.74. The data of this research were analyzed by using SPSS Program 16.0. Computation of the data T-counted result is 14.783, which means score was high than T-table result is 2.056. It means that the reading comprehension of VII grade at MTs Madinatul Ilmi DDI Siapo is improved.       Keywords: Improving, Reading comprehension, Preview, Question, Read, Summary, and Test method, Descriptive text